Rapid antimicrobial susceptibility testing (AST) based on in-situ time-lapse imaging of microcolonies - Meng, Siyu; Xu, Yiwen; Wang, Jingkai; Zhang, Zhiwei; Mao, Xin; Wang, Yimai; Zhang, Changsong; Wang, Ting; Shen, Yuanheng; Li, Hui; Zheng, Lesong; Wu, Qingqing; et al. (Sensors and actuators. B, Chemical, 2026)
Globally, bacterial infections cause over seven million deaths annually, often attributable to delayed or inappropriate antibiotic administration. Antimicrobial susceptibility testing (AST) is routinely performed in clinical settings to guide antibiotic therapy; however, current methods are limited by a minimum turnaround time of 16–20 h. Developing a rapid AST method based on bacterial morphological analysis could improve diagnostic efficiency and facilitate timely treatment for patients with severe bacterial infections. We developed an in-situ time-lapse imaging system for microcolonies (ISM-TLI). This system integrates an AST gel plate, a temperature-controlled incubation module capable of accommodating up to 30 patient samples simultaneously, a time-lapse imaging module, and integrated image processing algorithms. These algorithms perform image registration, microcolony identification, and minimum inhibitory concentration (MIC) interpretation. This system significantly reduces the turnaround time for obtaining AST profiles. A total of 21 antibiotics were tested on 9 reference strains, 24 clinical isolates and 2 urines samples, resulting in over 200 combinations. The concordance rates between the 2-hour and 3-hour TLI results and the broth microdilution (BMD) results were 90.8 % and 97.3 %, respectively. This system demonstrates the potential to shorten the existing clinical diagnostic process by over 14 h for isolates and 31–42 h for urine samples, significantly simplifying the process of guiding clinical antibiotic therapy. [Display omitted] •AST within 3 h by in-situ time-lapse imaging of microcolonies on 96-well gel plate.•Fully automated system processes the incubation and imaging for up to 30 strains.•Accuracy > 97 % for 9 reference strains and 24 clinical isolates against 21 antibiotics.•Direct detection of AST in urine samples reduced the TAT from 1.5 days to 2–3 h.